Elephantine, Ägypten. Gesamtprojekt Elephantine und Teilprojekt Lebenswirklichkeiten (Realities of Life). Die Arbeiten von Oktober 2017 bis Mai 2018 - Sigl, Johanna (e-Forschungsberichte des DAI, 2018)
Excavations in Middle Kingdom houses on Elephantine Island in the course of the DAI project “Realities of Life” revealed a variety of production activities, which were executed for the housing and provision of the inhabitants, but also hints on personal and commercial activities. The use of standard archaeological as well as archaeometric methods allow new and unexpected insight into e.g. jewelry and bread production, space utilization, and regional connections. The project also offers training programs and study days to support the capacity building of the employees of the Egyptian Ministry of Antiquities. Furthermore, a special exhibition on Arabic ostraca attesting to the history of Elephantine in the early Middle Ages was opened in the excavation museum.